Presentation: Ground Vibration Testing of a High Aspect Ratio Wing with Revolving Clamp - Dessena, Gabriele (Cranfield University, 2022)
This is the presentation delivered on the 8.9.2022 at the 33rd Congress of the International Council of the Aeronautical Sciences (ICAS) in Stockholm, Sweden. The presentation refers to the "Ground Vibration Testing of a High Aspect Ratio Wing with Revolving Clamp" paper that can be found at https://doi.org/10.17862/cranfield.rd.20486229
Keywords: Experimental Modal Analysis; 'Ground Vibration Testing'; 'High Aspect Ratio'; 'Structural Dynamics'; 'Flexible Wing'